Trade liberalization and regional integration in the Western Hemisphere : some policy issues - Bouzas, Roberto (FLACSO Buenos AiresAR, 1995)
Reviews the recent evolution of unilateral and perferential trade liberalisation in Latin America. Examines the role of external factors in perferential trade liberalisation in Latin America and addresses some policy dilemmas posed by the emergence of a North-South variety of economic integration in the Western Hemisphere. Discusses the stilised strategies being carried forward in the region and their implication for trade liberalisation.